13(3x-1)-2(8+6x)=52 x=?
Răspunsuri la întrebare
Răspuns de
4
13 ( 3 x - 1 ) - 2 ( 8 + 6 x ) = 52
39 x - 13 - 16 - 12 x = 52
27 x - 29 = 52
27 x = 52 + 29
27 x = 81
x = 81 : 27
x = 3
Răspuns de
3
13(3x-1)-2(8+6x)=52 ⇔ 39x-13-16-12x=52 ⇔ 39x-12x-29=52 ⇔ 27x=52+29 ⇔ 27x=81⇒x=81:27⇒x=3
Alte întrebări interesante
Matematică,
8 ani în urmă
Ed. tehnologică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă